2017
DOI: 10.1016/j.bpj.2017.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Electric-Field-Induced Protein Translocation via a Conformational Transition in SecDF: An MD Study

Abstract: SecDF is an important component of the Sec protein translocation machinery embedded in the bacterial membrane, which is associated with many functions, such as stabilizing other Sec translocon components within the membrane, maintaining the transmembrane (TM) potential, and facilitating the ATP-independent stage of the translocation mechanism. Related studies suggest that SecDF undergoes functionally important conformational changes that involve mainly its P1-head domain and that these changes are coupled with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…This results in reshaped local interactions and relative displacements between domains. Disruption of the secondary structure of S, particularly at the RBM, occurs under notoriously weaker EFs than those needed to produce significant changes in other proteins 26,28,32 . This suggests a possible causal link between structural vulnerability and affinity to ACE2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in reshaped local interactions and relative displacements between domains. Disruption of the secondary structure of S, particularly at the RBM, occurs under notoriously weaker EFs than those needed to produce significant changes in other proteins 26,28,32 . This suggests a possible causal link between structural vulnerability and affinity to ACE2.…”
Section: Discussionmentioning
confidence: 99%
“…It has been theoretically predicted and experimentally demonstrated that static and timedependent electric fields (EFs) are capable of inducing conformational changes [25][26][27][28][29][30] or even irreversible damage in proteins [31][32][33] . The fact that extremely intense EFs of strengths larger than 1Volt per nanometre (10 9 V m⁻¹) can denature entire proteins and even break chemical bonds is trivial and of little biological relevance.…”
mentioning
confidence: 99%
“…SecDF is thought to use the proton gradient for both the conformation switch and binding-release cycles (Tsukazaki et al 2011). This mechanism was supported by MD simulations (Ficici et al 2017), which concluded that the P1 head movement is regulated by the transmembrane potential. The barrier for such transition is lowered in the presence of the transmembrane potential Δψ.…”
Section: Introductionmentioning
confidence: 74%
“…Living systems naturally produce weak electric fields. Electrostatic forces, as long-range interactions, play a crucial role in defining the structure and properties of proteins [ 18 , 19 , 20 ]. Experimental studies have been carried out to understand the effect of an external environment on the protein properties, and even to explore the possibilities to control protein process via surface-enhanced resonance Raman spectroscopy (SERRS) [ 21 ], quartz crystal vibrational analysis (QCV) [ 22 ], the measurement of electrical double layer capacitance [ 23 , 24 ], etc.…”
Section: Introductionmentioning
confidence: 99%